A randomized, double-blind, placebo-controlled trial of simvastatin to treat Alzheimer disease - Sano, M. (Lippincott Williams & Wilkins, 2011)
BACKGROUND: Lowering cholesterol is associated with reduced CNS amyloid deposition and increased dietary cholesterol increases amyloid accumulation in animal studies. Epidemiologic data suggest that use of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) may decrease the risk of Alzheimer disease (AD) and a single-site trial suggested possible benefit in cognition with statin treatment in AD, supporting the hypothesis that statin therapy is useful in the treatment of AD. OBJECTIVE: To determine if the lipid-lowering agent simvastatin slows the progression of symptoms in AD. METHODS: This randomized, double-blind, placebo-controlled trial of simvastatin was conducted in individuals with mild to moderate AD and normal lipid levels. Participants were randomly assigned to receive simvastatin, 20 mg/day, for 6 weeks then 40 mg per day for the remainder of 18 months or identical placebo. The primary outcome was the rate of change in the Alzheimer's Disease Assessment Scale–cognitive portion (ADAS-Cog). Secondary outcomes measured clinical global change, cognition, function, and behavior. RESULTS: A total of 406 individuals were randomized: 204 to simvastatin and 202 to placebo. Simvastatin lowered lipid levels but had no effect on change in ADAS-Cog score or the secondary outcome measures. There was no evidence of increased adverse events with simvastatin treatment. CONCLUSION: Simvastatin had no benefit on the progression of symptoms in individuals with mild to moderate AD despite significant lowering of cholesterol. CLASSIFICATION OF EVIDENCE: This study provides Class I evidence that simvastatin 40 mg/day does not slow decline on the ADAS-Cog.